2022
DOI: 10.1080/19490976.2022.2046244
|View full text |Cite
|
Sign up to set email alerts
|

Dietary manipulation of the gut microbiome in inflammatory bowel disease patients: Pilot study

Abstract: Diet is a modifiable, noninvasive, inexpensive behavior that is crucial in shaping the intestinal microbiome. A microbiome “imbalance” or dysbiosis in inflammatory bowel disease (IBD) is linked to inflammation. Here, we aim to define the impact of specific foods on bacterial species commonly depleted in patients with IBD to better inform dietary treatment. We performed a single-arm, pre-post intervention trial. After a baseline period, a dietary intervention with the IBD-Anti-Inflammatory Diet (IBD-AID) was in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 148 publications
3
45
0
Order By: Relevance
“…P-gp is an evolutionarily conserved transporter and the host has evolved many pathways to maintain its expression in the intestinal epithelium due to its diverse and important roles in maintaining intestinal health. The intestinal microbiome contributes to maintenance of intestinal health, yet has been shown to fluctuate between various healthy states, often driven by environmental factors such as diet ( 58 , 79 81 ). The intestinal microbiome has evolved with the host, thus we hypothesize the activation of multiple signaling networks converging on P-gp transcription by this combination of microbiome-derived metabolites is a mechanism that has evolved between the bacteria and mammalian intestine in the context of the fluctuating commensal microbiome to ensure high expression of P-gp at the intestinal surface.…”
Section: Discussionmentioning
confidence: 99%
“…P-gp is an evolutionarily conserved transporter and the host has evolved many pathways to maintain its expression in the intestinal epithelium due to its diverse and important roles in maintaining intestinal health. The intestinal microbiome contributes to maintenance of intestinal health, yet has been shown to fluctuate between various healthy states, often driven by environmental factors such as diet ( 58 , 79 81 ). The intestinal microbiome has evolved with the host, thus we hypothesize the activation of multiple signaling networks converging on P-gp transcription by this combination of microbiome-derived metabolites is a mechanism that has evolved between the bacteria and mammalian intestine in the context of the fluctuating commensal microbiome to ensure high expression of P-gp at the intestinal surface.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Olendzki et al, the implementation of the diet in patients with Crohn’s disease allowed 60% of them to reduce their doses of medications used [ 120 ]. Another study showed a significant effect of the anti-inflammatory diet on the restoration of the intestinal microflora, including an increase in the levels of Faecalibacterium prausnitzii , Eubacterium eligens and Roseburia hominis , which are often found in too low amounts in patients with IBD [ 27 ].…”
Section: Specific Carbohydrates Diet and Anti-inflammatory Dietmentioning
confidence: 99%
“…Some reports have identified similarities in the composition of the microbiota in UC and CD, while others point to differences depending on the diagnosis [ 25 , 26 , 27 ]. The involvement of the intestinal microbiota in the onset, development and maintenance of the inflammatory process in IBD no longer raises any doubts.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the intake of prebiotics such as nondigestible fibers is positively correlated with circulating serum levels of granulocyte-macrophage colony stimulating factor (GM-CSF) and negatively correlated with interleukin (IL)-6 and IL-8. These cytokines play central roles in the pathogenesis of IBD [ 36 ] and could be a result of altered bacteria or bacterial metabolites in the intestinal lumen. Thus, an intimate relationship between host bacterial microbiome and epithelial cells is evident in the pathogenesis of IBD.…”
Section: Microbiome In the Pathogenesis Of Inflammatory Bowel Disease...mentioning
confidence: 99%